Orality and history in Portugal - Oliveira, L. T. de (Procedings of the International Conference on Oral Tradition. Orality and Cultural Heritage, 2010)
In this colloquium on orality and cultural heritage, prominence is given to folk literature and music as subjects for ethnographic and anthropological research. However, it is also useful to discuss the relevance of interviews, life stories and other oral methods forthese studies. Moreover, interviews may generally be considered as a research method for other Social Sciences, informing areas of studies in which it is not usually used. In Portugal, oral tradition, oral history, memory and post-memory have contributed to the development of new approaches in Cultural Studies and History. This paper will focus on the latter, more specifically, the emergence of oral history as an alternative working method in History.